Potent, structurally constrained agonists and competitive antagonists of corticotropin-releasing factor. - Gulyas, J (1995)
Predictive methods, physicochemical measurements, and structure activity relationship studies suggest that corticotropin-releasing factor (CRF; corticoliberin), its family members, and competitive antagonists (resulting from N-terminal deletions) usually assume an alpha-helical conformation when interacting with the CRF receptor(s). To test this hypothesis further, we have scanned the whole sequence of the CRF antagonist [D-Phe12,Nle21,38]r/hCRF-(12-41) (r/hCRF, rat/human CRF; Nle, norleucine) with an i-(i + 3) bridge consisting of the Glu-Xaa-Xaa-Lys scaffold. We have found astressin [cyclo(30-33)[D-Phe12,Nle21,38,Glu30,Lys33]r/ hCRF(12-41)] to be approximately 30 times more potent than [D-Phe12,Nle21,38]r/hCRF-(12-41), our present standard, and 300 times more potent than the corresponding linear analog in an in vitro pituitary cell culture assay. Astressin has low affinity for the CRF binding protein and high affinity (Ki = 2 nM) for the cloned pituitary receptor. Radioiodinated [D-125I-Tyr12]astressin was found to be a reliable ligand for binding assays. In vivo, astressin is significantly more potent than any previously tested antagonist in reducing hypophyseal corticotropin (ACTH) secretion in stressed or adrenalectomized rats. The cyclo(30-33)[Ac-Pro4,D-Phe12,Nle21,38,Glu30,Lys33++ +]r/hCRF-(4-41) agonist and its linear analog are nearly equipotent, while the antagonist astressin and its linear form vary greatly in their potencies. This suggests that the lactam cyclization reinstates a structural constraint in the antagonists that is normally induced by the N terminus of the agonist.